Charge injection driven switching between ferromagnetism and antiferromagnetism in transitional metal-doped MoS2 materials. (27th October 2017) - Song, Changsheng; Pan, Jiaqi; Wu, Xiaoping; Cui, Can; Li, Chaorong; Wang, Jiqing
Abstract: Using first-principles calculations, we report on charge injection induced switching between ferromagnetic (FM) and antiferromagnetic (AFM) in a 2H- M o S 2 monolayer. M o S 2 monolayers doped with different transition metals (TM)—Fe and Mn—initially demonstrate FM and AFM magnetic ground state, respectively. Once the injected charge approaches 1.0 e/unit, the systems respectively tend to AFM and FM states, due to the modulation effect of the exchange splitting of spins via injected charge. The interesting switch between FM and AFM can be explained by the competition between FM double-exchange and AFM super-exchange interaction. In contrast, the M o S 2 / W S 2 heterojunction, because of the direct bonding between dopant TM atoms, remains in the AFM state even under charge injection. These findings point toward the possible development of spintronic switch devices using charge injection in TM doped M o S 2 materials, which could be pivotal to information storage and spintronic applications.